Point prevalence survey of healthcare-associated infections and antimicrobial use in Kosovo hospitals - Lul Raka; Gazmend Spahija; Agreta Gashi-Gecaj; Astrit Hamza; Edita Haxhiu; Albiona Rashiti; Gëzim Rrahimi; Selvete Hyseni; Nicola Petrosillo (MDPI AG, 2019)
Health care-associated infections (HAIs) and antimicrobial resistance constitute a major public health challenge. The aim of this study was to assess the prevalence rate of HAIs and antimicrobial use in acute care hospitals in Kosovo. A multicenter study was performed in all hospitals in Kosovo. The standardized protocol for Point Prevalence Survey (PPS) on HAIs and antimicrobial use developed by European Center for Disease Control and Prevention (ECDC) was used for this survey. A total of 915 patients were included in PPS. Countrywide prevalence rate of HAIs was 4.9%. The highest rate was noticed in tertiary care level in University Clinical Centre of Kosovo (UCCK) (7.2%). The most common type of HAI was surgical site infection, representing 35.5% of all reported HAIs. Prevalence of HAIs was highest in surgical departments (46.6%). The median length of stay before onset of HAI was 11 days (range: 3-27 days). Gram negative bacteria were the predominant microorganisms (61% of cases). From all patients, 520 (56.8%) of them were using at least one antibiotic. Ceftriaxone was the most prescribed antibiotic with 40.3%. Antibiotics were administered mainly through parenteral route (93.8%). Empiric treatment was the physician's choice for prescribing in 87.1%. The main reason for antibiotic treatment was pneumonia (19.8%). Medical prophylaxis was reported in 10% of antibiotic prescriptions. Key recommendations driven by this study are to improve surveillance systems of HAI and antibiotic use, enhance infection prevention and control and establish antimicrobial stewardship program.